A new β0‐thalassemia frameshift mutation [β 48 (‐T)] in a Uruguayan family. Issue 1 (17th August 2012) - Da Luz, J.; López, P.; Kimura, E. M.; Albuquerque, D. M.; Costa, F. F.; Sans, M.; Sonati, M. F.
Summary We describe here a new frameshift mutation of β‐thalassemia in a Uruguayan family with Italian ancestry [β48 (‐T); HBB:c.146delT]. This frameshift results in formation of premature stop codon (TGA) 40 bp downstream and in a short unstable product that is degraded in the cell.